Anhydrites from gypsum cap-rock of Zechstein salt diapirs - Jaworska, Joanna; Nowak, Monika (Geology, Geophysics and Environment, 2013)
Petrographic studies of gypsum cap-rock formations of the Wapno, Dębina, Mogilno (Poland) and Gorleben (Germany) salt domes indicate that the occurrence of anhydrite in the domes, in the form of both single grains which sometimes create an anhydritic sandstone bed in the bottom section of the cap-rocks, and massive fragments or anhydrite rocks (detached blocks), most often represent the Main Anhydrite formations. Both types of anhydrites: - can be distinguished owing to their different structures and textures, - are subjected to the gypsification process, although anhydrite sand and sandstone are transformed quickly, while detached blocks of anhydrite very slowly. Residuum anhydrites are concentrated in the cap-rock bottom and/or dispersed in coarse-crystal gypsums, while detached blocks occur irregularly.